Effectiveness and Safety of Biosimilars in Pediatric Non-infectious Uveitis: Real-Life Data from the International AIDA Network Uveitis Registry - Maria Tarsia; Antonio Vitale; Carla Gaggiano; Jurgen Sota; Anna Maselli; Chiara Bellantonio; Silvana Guerriero; Rosanna Dammacco; Francesco La Torre; Gaafar Ragab; Mohamed Tharwat Hegazy; Alex Fonollosa; et al. (Ophthalmology and Therapy, 2024)
Abstract Introduction Since many biological drug patents have expired, biosimilar agents (BIOs) have been developed; however, there are still some reservations in their use, especially in childhood. The aim of the current study is to evaluate the efficacy and safety of tumor necrosis factor (TNF) inhibitors BIOs as treatment for pediatric non-infectious uveitis (NIU). Methods Data from pediatric patients with NIU treated with TNF inhibitors BIOs were drawn from the international AutoInflammatory Disease Alliance (AIDA) registries dedicated to uveitis and Behçet's disease. The effectiveness and safety of BIOs were assessed in terms of frequency of relapses, risk for developing ocular flares, best-corrected visual acuity (BCVA), glucocorticoids (GCs)-sparing effect, drug survival, frequency of ocular complications, and adverse drug event (AE). Results Forty-seven patients (77 affected eyes) were enrolled. The BIOs employed were adalimumab (ADA) (89.4%), etanercept (ETA) (5.3%), and infliximab (IFX) (5.3%). The number of relapses 12 months prior to BIOs and at last follow-up was 282.14 and 52.43 per 100 patients/year. The relative risk of developing ocular flares before BIOs introduction compared to the period following the start of BIOs was 4.49 (95% confidence interval [CI] 3.38–5.98, p = 0.004). The number needed to treat (NNT) for ocular flares was 3.53. Median BCVA was maintained during the whole BIOs treatment (p = 0.92). A significant GCs-sparing effect was observed throughout the treatment period (p = 0.002). The estimated drug retention rate (DRR) at 12-, 24-, and 36-month follow-up were 92.7, 83.3, and 70.8%, respectively. The risk rate for developing structural ocular complications was 89.9/100 patients/year before starting BIOs and 12.7/100 patients/year during BIOs treatment, with a risk ratio of new ocular complications without BIOs of 7.1 (CI 3.4–14.9, p = 0.0003). Three minor AEs were reported. Conclusions TNF inhibitors BIOs are effective in reducing the number of ocular uveitis relapses, preserving visual acuity, allowing a significant GCs-sparing effect, and preventing structural ocular complications. Trial Registration ClinicalTrials.gov ID NCT05200715.